2022
DOI: 10.1037/rev0000340
|View full text |Cite
|
Sign up to set email alerts
|

Self-validation theory: An integrative framework for understanding when thoughts become consequential.

Abstract: Self-validation theory (SVT) is introduced and presented as a series of six postulates. The core notion of SVT is that thoughts become more consequential for judgment and action as the perceived validity of the thoughts is increased. Instead of focusing on the objective accuracy of thoughts, self-validation research focuses on a subjective sense that one’s thoughts are valid or appropriate to use. People come to rely on any thought more when they perceive that thought is likely to be true (cognitive validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 173 publications
(292 reference statements)
2
33
0
Order By: Relevance
“…Once the theory of the self is consolidated, individuals gradually assign increasing weights to their self-concept to facilitate its maintenance at the expense of continuous updating. Inner models (priors) such as the self-concept and the predictions they make affect, in turn, how people interact with the world and how such interactions affect their previous priors (for a review see Briñol and Petty, 2021 ). The priors and their precision come into play, for instance, when credible or non-credible sources validate (or invalidate) previous beliefs (Tormala et al, 2006 ) or when predicting other’s actions (for a review see Bach and Schenke, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once the theory of the self is consolidated, individuals gradually assign increasing weights to their self-concept to facilitate its maintenance at the expense of continuous updating. Inner models (priors) such as the self-concept and the predictions they make affect, in turn, how people interact with the world and how such interactions affect their previous priors (for a review see Briñol and Petty, 2021 ). The priors and their precision come into play, for instance, when credible or non-credible sources validate (or invalidate) previous beliefs (Tormala et al, 2006 ) or when predicting other’s actions (for a review see Bach and Schenke, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is very important, because the absence of that instruction may increase the likelihood of thinking about either positive or negative elements of using condoms in similar quantities or even negative thoughts about condoms. In the first case, thoughts may lead to positive and negative evaluations simultaneously, leading to attitude uncertainty, which reduces the impact on BI’s [ 37 ]. In the second case, by generating mostly negative thoughts, attitudes toward condom use may also be negative and might predict unhealthy behaviors such as avoiding the use of condoms.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, thoughts lead to judgments and evaluations (i.e., attitudes) about the object that are consistent with thought favorability. In other words, to understand subsequent attitudes and behaviors, the direction of the message is less important than the direction of what people think [ 19 , 34 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed consistently that thoughts with a positive valence lead to favorable attitudes and that the opposite occurs for negative valence thoughts, especially when people have the opportunity and motivation to engage in systematic thinking [21,28]. In order to study thought favorability, Killeya and Johnson [22] proposed and demonstrated that thinking about an object in a specific direction (positive or negative) leads to an attitude change in line with those thoughts.…”
mentioning
confidence: 99%
“…Following the elaboration likelihood model of persuasion (ELM, [21]), it could be that high presence in a virtual experience, since it is a positive feeling, might reduce the motivation to think and the effect of thought direction. It also might be the case that presence affects the validity of thoughts [28], reducing their impact on attitudes, especially with the negative ones ("I thought that museums are bad, but after the experience, I seriously doubt that"). In any case, our results show that the analysis of the effect of a virtual museum on attitudes toward cultural heritage is not derived only by simple effects, but especially for interactions that can guide some theoretical explanations for the observed consequences.…”
mentioning
confidence: 99%